HUBUNGAN NYERI ARTRITIS RHEUMATOID DENGAN TINGKAT KEMANDIRIAN PADA LANSIA DI WILAYAH KERJA PUSKESMAS KAMPAR TAHUN 2020 - ANNISAK NUZUL; ALINI ALINI; PUTRI EKA SUDIARTI (Universitas Pahlawan Tuanku Tambusai, 2020)
Elderly is someone who has entered the age of> 60 years and over has decreased ability to live or limited physical activity. The pain that is felt so strong will cause impaired independence so that it can reduce the cognitive abilities of the elderly which can cause the elderly to become dependent. The purpose of this study was to determine the relationship between rheumatoid arthritis pain and the level of independence of the elderly in the work area of the Kampar Public Health Center in 2020. This study used an analytical research design with a cross sectional design. The sample in this study was the elderly aged > 60 as many as 85 people. data collection through questionnaires. Data processing used univariate and bivariate analysis with the Chi-Square test. The results showed that there was a significant relationship between rheumatoid arthritis pain and the level of independence in the elderly with p value = 0.000. With this research, researchers hope that health workers can improve the quality of service, especially for the elderly.